2017
DOI: 10.1111/ggi.13146
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of physical inactivity, loss of muscle mass and low dietary intake: Extrapulmonary manifestations in older chronic obstructive pulmonary disease patients

Abstract: Aim: Extrapulmonary manifestations, such as reductions in skeletal muscle and physical inactivity, are important clinical features of patients with chronic obstructive pulmonary disease (COPD), and might depend on the severity of COPD. As it is still unclear whether the relationship between muscle loss and physical inactivity is dominated by a disease-specific relationship or caused by patient factors, including physiological aging, we aimed to investigate the pulmonary or extrapulmonary factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Skeletal muscle function plays an important role in the exercise capacity and activities of daily living and can be used to predict the mortality of COPD patients independent of lung function 1,7,8. Currently, the primary means of assessing skeletal muscle function include isometric, isotonic, and isokinetic test.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle function plays an important role in the exercise capacity and activities of daily living and can be used to predict the mortality of COPD patients independent of lung function 1,7,8. Currently, the primary means of assessing skeletal muscle function include isometric, isotonic, and isokinetic test.…”
Section: Introductionmentioning
confidence: 99%
“…This negative result may be attributable to missing CT data and discrepancies in structure–function relationships. In our previous study, physical activity was significantly associated with diffusing capacity but not with LAA% . Fourth, we could not find an explanation for why ΔA‐aDO 2 was not a better index than ΔPaO 2 .…”
Section: Discussionmentioning
confidence: 59%
“…In our previous study, physical activity was significantly associated with diffusing capacity but not with LAA%. 26 Fourth, we could not find an explanation for why ΔA-aDO 2 was not a better index than ΔPaO 2 . Regarding Á V/ Á Q mismatch, we expected ΔA-aDO 2 to be associated more strongly with CRF development.…”
Section: Discussionmentioning
confidence: 76%
“…That functional status can be considered a marker of disease severity is not only obvious from the disease trajectory analysis, but also from data coming from various clinical studies on COPD patients: dyspnea severity was found to be inversely correlated with functional status and to be a major limiting factor to physical activity. Among extra-respiratory symptoms, fatigue was found to be associated with impaired exercise capacity in patients with more advanced COPD, irrespective of age or sex [ 5 , 6 , 7 , 8 ].…”
Section: Functional Status and Copdmentioning
confidence: 99%